Nahdlatul Ulama Dalam Polemik Nasab Habib Ba'alawi - Amir Mahmud (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This research investigates Nahdlatul Ulama's (NU) views on the Habib Ba Alawi lineage polemic, focusing on how Indonesia's largest Islamic organization manages and responds to historical claims related to the lineage. This study aims to understand NU's approach to historical and religious issues affecting Islamic identity in Indonesia and how these views influence the historical narratives inherited by the NU community. This research uses a descriptive qualitative approach with a literature analysis of multiculturalism in post- independence Indonesia. The conclusion of the research shows that the determination of lineage during the time of the Prophet and the Companions was done based on the validity of the parents' marriage and methods such as Qa-fah and al-qiyafa. The controversy over the Bani Alawi lineage reveals the complexity in verifying genealogical claims and shows the dynamics in Islamic history. In Indonesia, pesantren play an important role in Islamic education while maintaining tradition and culture. The suggestions emphasize the need for a rigorous scientific approach in the verification of lineage claims and respect for long- established cultural values.